The Medication Adherence Report Scale: A measurement tool for eliciting patients' reports of nonadherence. Issue 7 (18th May 2020) - Chan, Amy Hai Yan; Horne, Rob; Hankins, Matthew; Chisari, Claudia
Abstract : Aims: This study aimed to establish the psychometric properties of a questionnaire measure of patients' adherence to medications to elicit patients' report of medication use in a variety of clinical samples. The reliability and validity were assessed in patients with hypertension. Additional analyses were performed on other patient groups. Methods: Using a cross‐sectional study design, a 10‐item version of the Medication Adherence Report Scale (©Professor Rob Horne) was piloted in two samples of patients receiving treatment for hypertension (n = 50 + 178), asthma (n = 100) or diabetes (n = 100) at hospital outpatient or community clinics in London and the south‐east of England. Following principal components analysis, five items were retained to form MARS‐5 (©Professor Rob Horne). Evaluation comprised internal reliability, test‐retest reliability, criterion‐related validity (relationship with blood pressure control) and construct validity (relationship with patients' beliefs about medicines). Results: The MARS‐5 demonstrated acceptable reliability (internal and test‐retest) and validity (criterion‐related and construct validity) in these patient groups. Internal reliability (Cronbach's α) ranged from 0.67 to 0.89 across all patient groups; test‐retest reliability (Pearson's r ) was 0.97 in hypertension. Criterion‐related validity was established with more adherent hypertension patients showing better blood‐pressure control (χ 2 = 4.24, df = 1, P < .05). Construct validity with beliefs about medicines was demonstrated with higher adherence associated with stronger beliefs in treatment necessity and lower treatment concerns. Conclusions: The MARS‐5 performed well on several psychometric indicators in this study. It shows promise as an effective self‐report tool for measuring patients' reports of their medication use across a range of health conditions.